Systems biology and proteomic analysis of cerebral cavernous malformation. (June 2014) - Edelmann, Alexander R; Schwartz-Baxter, Sarah; Dibble, Christopher F; Byrd, Warren C; Carlson, Jim; Saldarriaga, Ivandario; Bencharit, Sompop
<x xml:space="preserve">Abstract</x> Cerebral cavernous malformations (CCM) are vascular anomalies caused by mutations in genes encoding KRIT1, OSM and PDCD10 proteins causing hemorrhagic stroke. We examine proteomic change of loss of CCM gene expression. Using human umbilical vein endothelial cells, label-free differential protein expression analysis with multidimensional liquid chromatography/tandem mass spectrometry was applied to three CCM protein knockdown cell lines and two control cell lines: ProteomeXchange identifier PXD000362. Principle component and cluster analyses were used to examine the differentially expressed proteins associated with CCM. The results from the five cell lines revealed 290 and 192 differentially expressed proteins (p < 0.005 and p < 0.001, respectively). Most commonly affected proteins were cytoskeleton-associated proteins, in particular myosin-9. Canonical genetic pathway analysis suggests that CCM may be a result of defective cell–cell interaction through dysregulation of cytoskeletal associated proteins. Conclusion: The work explores signaling pathways that may elucidate early detection and novel therapy for CCM.